Cyclosporin a reduces the severity of cold-restraint- induced gastric lesions: Role of leukocytes - YEGEN, BERRAK (My University, 1995)
The objective of this study was to determine the role of cyclosporin A (CsA) on cold-restraint-induced gastric lesions. Animals were subjected to 3 h immobi lization at 4°C in plastic restraining devices following a starvation period of 48 h. Gastric samples were obtained for the measurement of myeloperoxidase (MPO) activity, an index of number of peroxidase positive cells and thiobarbi- turic acid-reactive substances (TBARS; lipid peroxidation). Animals were pre-treated with CsA which is a potent immunosuppressant and inhibits ischemia/ reperfusion-induced polymorphonuclear leukocyte (PMN) infiltration. Coldrestraint administration significantly elevated the tissue MPO activity and TBARS formation. CsA pretreatment significantly reduced the severity of cold-restraint-induced gastric lesions while attenuating the elevated MPO measurements observed during cold-restraint administration. Animals ren-dered neutropenic with antineutrophil serum (ANS) exhibited significantly less gastric mucosal injury normally observed after cold-restraint stress. Nei ther CsA nor ANS treatment effected the elevated TBAR levels, indicating that PMNs are not involved in the lipid peroxidation process observed after cold-restraint stress. In conclusion, the results of this study indicate that CsA is capable of inhibiting cold-restraint-induced gastric mucosal injury and can attenuate the cold-restraint-induced increases in gastric MPO measurements. Our results also indicate that PMNs may be the important mediators of coldrestraint-induced gastric lesions. © 1995 S. Karger AG, Basel.
Keywords: Cold restraint; Cyclosporin A; Myeloperoxidase; Polymorphonuclear leukocytes